Binema bonaerensis n. sp. (Oxyurida: Thelastomatidae) parasite of Neocurtilla claraziana saussure (Orthoptera: Gryllotalpidae) in Argentina - Nora B Camino; Guillermo R Reboredo (Memorias do Instituto Oswaldo Cruz, 1999)
The nematode Binema bonaerensis n. sp. (Oxyurida: Thelastomatidae) is described from the intestine of the mole cricket of Neocurtilla claraziana Saussure (Orthoptera: Gryllotalpidae) from Buenos Aires Province, Argentina. It is distinguished mainly by having a conical tail; three sclerotized arches in the buccal cavity; an excretory pore inmediately posterior to the base of the esophagus and the presence of five pairs of male genital papillae with one pair preanal and four pairs postanal.